Is corporate social responsibility pursuing pristine business goals for sustainable development? - Hoque N.; Rahman A.R.A.; Molla R.I.; Noman A.H.M.; Bhuiyan M.Z.H. (John Wiley and Sons Ltd, 2024)
There is a continuing academic debate on corporate social responsibility (CSR), its goals and practices, and its impact on business and society. Following this debate, this study has made a critical investigation of CSR practices of business enterprises with a view to examining their spirit, intentions and roles in terms of pristine business goals. After analyzing the contents of pertinent literature (126 articles, of which 89 are empirical) in both developed and developing country contexts, the study finds that corporate managers are still less concerned about the meaning and essence of pristine business goals and the true goals and role of CSR. They practice CSR largely in a voluntary philanthropic fashion to build public image and primarily enhance business profit, not necessarily for social wellbeing. Their CSR practices have been found to be more of a cosmetic and face-saving marketing strategy, undermining the social wellbeing goal for sustainable development. The CSR movement, therefore, needs reformation. Copyright 2018 John Wiley & Sons, Ltd and ERP Environment